Self-appreciation is not enough: exercise identity mediates body appreciation and physical activity and the role of perceived stress - Shi, Linyu; Jiang, Lixia; Zhou, Song; Zhou, Wenbo; Yang, Huaqi (Frontiers in Psychology, 2024)
Introduction This study explores the relationship between body appreciation and physical activity, focusing on the mediating role of exercise identity and the moderating effect of perceived stress. While individuals with positive body image are generally thought to engage in proactive physical activity, it remains unclear whether this positive attitude necessarily promotes exercise. Methods We conducted a short-term longitudinal survey, recruiting 345 college students 28 (100 females, 245 males; Mage = 22.94, SD = 5.99) who completed questionnaires at two-week intervals for a total of three times within four weeks. Body appreciation, exercise identity, perceived stress, and physical activity were measured for the participants separately. Results The results demonstrated that body appreciation positively predicted physical activity, exercise identity partially mediated the positive effect of body appreciation on physical activity, and perceived stress played a moderating role in body appreciation and exercise identity. Discussion These results highlight the significant role of body appreciation in influencing physical activity through exercise identity, with perceived stress further moderating this relationship. The study underscores the importance of promoting body appreciation and regulating stress to enhance physical activity engagement among college students.